Towards a Universal History of Antiquarians - Schnapp, Alain (Complutum, 2013)
Historians of archaeology have traditionally seen antiquarianism in opposition to archaeology. According to this view, archaeology came of age at the beginnings of the 19th century when European scholars were able to take the great step forward that bridged the gap between antiquarianism and archaeology. In this paper, I explore the history of antiquarian research from classical antiquity until the 18th century. In particular, I examine how the notion of antiquarianism has articulated an understanding of the relationship between memory and forgetting that is essential to understand modern conceptions of the past.